Study on reservoir characteristics of Chang2 reservoir in southwest Ordos Basin - Fan, Xuandu; Ma, Jiaxuan; Ren, Xingjian (International Journal of Electric Power and Energy Studies, 2023)
In order to clarify the reservoir characteristics of the Chang2 oil formation in the GQ block of the Ordos Basin, the reservoir characteristics and pore structure of the Long 2 oil formation in the study area were investigated using experimental data such as cast thin section, scanning electron microscope (SEM) and mercury pressure curve. The results show that the Chang2 oil formation in the study area mainly develops medium sandy fine-grained feldspathic sandstone, and the pore types are rock dissolution pores and intergranular pores. The reservoirs of the Chang2 oil formation group in the study area were evaluated and classified by applying piezomercury curve banding, and the reservoirs were classified into three categories: Small pore-medium fine-throat type-medium pore-medium fine-throat type, Fine pore-micro-throat type and Mesoporous-coarse throat type. In the study area, most of the reservoirs in Chang2 are Small pore-medium fine-throat type-medium pore-medium fine-throat type, accounting for 50% of the total, while Mesoporous-coarse throat type accounts for 34.7% and Fine pore-micro-throat accounts for 15.3% of the total. The Chang2 oil reservoir in the study area is mainly developed as a general reservoir.